Clinical Pharmacokinetics and Pharmacodynamics of Etelcalcetide, a Novel Calcimimetic for Treatment of Secondary Hyperparathyroidism in Patients With Chronic Kidney Disease on Hemodialysis. (13th March 2018) - Wu, Benjamin; Melhem, Murad; Subramanian, Raju; Chen, Ping; Jaramilla Sloey, Bethlyn; Fouqueray, Bruno; Hock, M. Benjamin; Skiles, Gary L.; Chow, Andrew T.; Lee, Edward
Abstract: Etelcalcetide, a d ‐amino acid peptide, is an intravenous calcimimetic approved for the treatment of secondary hyperparathyroidism. Etelcalcetide binds the calcium‐sensing receptor and increases its sensitivity to extracellular calcium, thereby decreasing secretion of parathyroid hormone (PTH) by chief cells. Etelcalcetide and its low‐molecular‐weight transformation products are rapidly cleared by renal excretion in healthy subjects, but clearance is substantially reduced and dependent on hemodialysis in end‐stage renal disease. The effective half‐life is 3–5 days in patients undergoing hemodialysis 3 times a week. A clinical study using a single microtracer intravenous dose of [ 14 C]etelcalcetide indicated that 60% of the administered dose was eliminated in dialysate. Etelcalcetide undergoes reversible disulfide exchange with serum albumin to form a serum albumin peptide conjugate that is too large (67 kDa) to be dialyzed, until a subsequent exchange forms etelcalcetide or a low‐molecular‐weight transformation product. This exchange from albumin is apparent after hemodialysis, when it partially restores etelcalcetide concentrations in plasma. Etelcalcetide has no known risks for drug–drug interactions. In phase 3 studies, 74%–75% of hemodialysis patients with secondary hyperparathyroidism who received etelcalcetide achieved a >30% PTH reduction from baseline versus 8%–10% of patients who received placebo. The pharmacokinetics and pharmacodynamics of etelcalcetide in hemodialysis patients supports a 5‐mg starting dose administered after hemodialysis and uptitration in 2.5‐ or 5‐mg increments every 4 weeks to a maximum dose of 15 mg 3 times a week.